Highly photo-stable CsPbI3 perovskite quantum dots via thiol ligand exchange and their polymer film application - Baek, Seungmin; Kim, Yongjin; Kim, Sang Wook (Journal of Industrial and Engineering Chemistry, 2020)
Highly photo-stable CsPbI3 perovskite quantum dots (PeQDs) were prepared using thiol as an exchanged ligand. Among the CsPbX3 PeQDs, CsPbI3 with common capping ligands such as oleic acid (OA) and oleylamine (OLA) was particularly unstable and the optical properties were readily degraded because of its structural instability. To overcome these problems, thiol (–SH) as an exchanged ligand was used to stabilize the structure and could maintain the structural and optical properties. The synthesized CsPbI3 exhibited highly improved photo-stability under ultraviolet (365 nm) irradiation by ligand exchange from OA and OLA to thiol. As an application, perovskite films were fabricated using the PeQDs and a cyclic olefin copolymer (COC). The thiol-treated PeQD films exhibited higher stability than the untreated films under irradiation with a blue light-emitting diode (LED).
Keywords: Blue light emitting diodes; Cyclic Olefin Copolymers; Ligand exchanges; Perovskite films; Photo-stability; Structural and optical properties; Structural instability; Thiol-capped; Ligand exchange; Photo-stability; QD films; Thiol-capped CsPbI3 perovskite quantum dots